Discipline and Incentives on Employee Performance - Andi Makkulawu Panyiwi Kessi; Megawaty Megawaty; Hendriadi Hendriadi (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to empirically analyze the influence of discipline and incentives on employee performance at Perumda Air Minum Kota Makassar (PDAM Makassar). This study seeks to explain the extent to which these two factors contribute to improving employee performance in public service organizations. Research Method: This study employed a quantitative approach, relying on primary data collected via questionnaires distributed to employees of Perumda Air Minum Kota Makassar. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The analytical procedure evaluated both the measurement and structural models, followed by a bootstrapping technique to test the direct and simultaneous effects statistically. Results and Discussion: The results show that discipline has a positive and significant effect on employee performance, indicating the importance of rule compliance and consistent work behavior in improving performance. Conversely, incentives have a positive but insignificant effect, indicating they are not strong enough to encourage improved performance. These findings confirm that non-financial factors, such as discipline, are more decisive in determining performance in public organizations like PDAM. Implications: This study provides practical guidance for PDAM to maintain and strengthen its work-discipline culture, a key strategy for improving performance. In addition, the company needs to evaluate its incentive system to ensure that it is more relevant, fair, and directly linked to performance achievements.